Constipation : a practical approach to diagnosis and treatment - Rose, MD, MSEd, Suzanne (Springer New York, 2014)
Constipation: A Practical Approach to Diagnosis and Treatment serves as an unmet resource for physicians and other health care providers, including trainees and students, who see patients with constipation. The text reviews pathophysiologic mechanisms and details evaluation and management strategies. The volume also enables the reader to identify epidemiologic factors and quality of life parameters for patients with constipation, discuss differences in pathophysiologic mechanisms for different etiologies of constipation, recognize primary causes of constipation, and assess special considerations related to the symptom of constipation including presentations in the elderly, in pregnant women, in patients with systemic diseases, and patients with a history of abuse. Written by thought leaders and recognized experts in gastrointestinal motility and medical education, Constipation: A Practical Approach to Diagnosis and Treatment is of great value and utility for gastroenterologists, primary care physicians, gynecologists, nurse practitioners, physician's assistants, as well as fellows and residents.